DEVELOPMENT OF A POWDER MIXTURE FOR PREPARING A DRINK WITH INGREDIENTS THAT PROMOTE INCREASE COGNITIVE ENDURANCE - Chernenko , Софія (Biota. Human. Technology, 2025)
The aim of this work was to develop an instant powdered beverage enriched with microencapsulated polyphenols and neuro-supportive nutrients to enhance cognitive endurance under combat-related stress. The product is intended for use by military personnel operating in extreme environments that impair mental performance. Methodology: The beverage formulation included epigallocatechin gallate (EGCG), L-tyrosine, caffeine, L-theanine, zinc citrate, and berry-derived anthocyanins. Polyphenols were microencapsulated using sodium alginate, gelatin, and maltodextrin, followed by freeze-drying. To reduce the bitterness of L-tyrosine and EGCG, a masking matrix based on maltodextrin and whey protein isolate was developed. The samples were analyzed for antioxidant activity (DPPH, FRAP), individual polyphenol content (HPLC), sensory attributes, solubility, and physical stability during 30-day storage. Scientific novelty: This study presents an integrated approach combining microencapsulation, matrix masking, and functional formulation tailored to cognitive needs in high-stress settings. For the first time, a freeze-dried beverage matrix was designed to stabilize both EGCG and anthocyanins while simultaneously masking L-tyrosine bitterness without advanced encapsulation systems. Conclusions: The developed beverage demonstrated high antioxidant activity, excellent solubility, and sensory acceptability. Microencapsulation significantly improved the retention of polyphenols and organoleptic quality. The formulation proved stable for at least 30 days at room temperature. The combination of ingredients was scientifically justified and technologically feasible. The product has potential for use in military nutrition as a convenient and effective means to support cognitive performance and endurance during prolonged stress.